ICASSP 2021 - 2021 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2021
DOI: 10.1109/icassp39728.2021.9414683
|View full text |Cite
|
Sign up to set email alerts
|

A Wireless Reference Active Noise Control Headphone Using Coherence Based Selection Technique

Abstract: Feedforward active noise control (ANC) is widely utilized to attenuate the broadband noise picked up by the reference microphone. However, in some situations, it is impractical to obtain a clean reference signal when the noise source is far away from the controller. Hence, we adopt a wireless reference microphone to pick up the reference signals around the noise sources. Furthermore, a coherence-based-selection algorithm is proposed to select the reference signals with high coherence. The proposed method impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…where C 1 (k) denotes the power spectral ratio of the specified mirror noise with respect to the actually received mirror noise, and P t,k (m) denotes multiplication of the maximum value of Ŝee,k (m) (where 0 < k < k L 2 ) when weighted by the equal-response curve A(k) [20]. If the primary sound source has weak high-frequency content, the upper limit of the allowed power spectrum of the mirror noise is given by P t,k (m).…”
Section: Data-driven Dynamic Matching Of Reconstruction Filtersmentioning
confidence: 99%
See 1 more Smart Citation
“…where C 1 (k) denotes the power spectral ratio of the specified mirror noise with respect to the actually received mirror noise, and P t,k (m) denotes multiplication of the maximum value of Ŝee,k (m) (where 0 < k < k L 2 ) when weighted by the equal-response curve A(k) [20]. If the primary sound source has weak high-frequency content, the upper limit of the allowed power spectrum of the mirror noise is given by P t,k (m).…”
Section: Data-driven Dynamic Matching Of Reconstruction Filtersmentioning
confidence: 99%
“…With the increase in local active noise control systems in practical application scenarios, more discussions about group delay and causality have been conducted [17][18][19]. In order to avoid the limitations imposed by the spatial distance on the group delay, Shen et al proposed an increase in the distance between the reference microphone and the error microphone using wireless transmission [20]. However, this method does not allow for long-frame caching and has extremely demanding delay requirements for the wireless transmission system.…”
Section: Introductionmentioning
confidence: 99%
“…The core idea was similar to the previous work in [38], but emphasis was placed on the wireless relay design, in which an analog frequency modulator was adopted to bypass delays from digitization and processing. In 2021, Shen et al worked out a coherence-based selection algorithm of wireless reference microphones when there were two distant noise sources operating at different times [40]. In their work, the wireless relay and the motivation of employing the wireless reference microphone were fundamentally similar to the MUTE system.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the experiment conducted in real-time indicated that ASHANC could reduce both the broadband noise and interference present in the environment and achieved a noise reduction level that was 4 − 8 dB better than the commercial headphone. mance of wireless ANC [63] and is expanded to multi-channel wireless ANC [64] in Section 5.4. A coherence-based weight determination algorithm [75] is proposed to improve the multi-channel wireless ANC in Section 5.5.…”
Section: Discussionmentioning
confidence: 99%
“…2.15. If the headphone's look-ahead time is several milliseconds, the ANC has enough time to process and generate anti-noise [63,64].…”
Section: Wireless Transmission Applied In Ancmentioning
confidence: 99%